ANALISIS PENGAKUAN PENDAPATAN ATAS JASA KONSTRUKSI PADA PT. EVA MAHKOTA PURA - Kurniawati, Erna; Leiwakabessy, Pitter; Saroan, Melisa (Jurnal Pitis AKP, 2021)
This study was conducted to determine the analysis of revenue recognition based on the Statement of Financial Accounting Standards (PSAK 72). The results of the study indicate that PT. Eva Mahkota Pura has implemented PSAK 72 using the over time method. And apply (Physical Progress) the physical method in recognizing revenue which is based on the results of units of output. The company measures the value of the recognized contract by subtracting the value in accordance with the contract agreement with DPP (Basic of Taxation) which includes VAT (Value Added Tax) and Final PPH (Income Tax).